2010
DOI: 10.15288/jsad.2010.71.326
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Posttraumatic Stress Symptoms, and Alcohol-Use Initiation in Children

Abstract: ABSTRACT. Objective: This study examined initiation of alcohol use among adolescents, in relation to their earlier traumatic experiences and symptoms of posttraumatic stress disorder (PTSD). Method: Data were from a longitudinal study of children of Puerto Rican background living in New York City's South Bronx and in San Juan, Puerto Rico. The subsample (n = 1,119; 51.7% male) of those who were 10-13 years old and alcohol naive at baseline was used in the analyses. Results: Alcohol-use initiation within 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
2
19
1
Order By: Relevance
“…One focused on depressive symptoms (Wu et al 2006) and another on trauma and post-traumatic stress disorder symptoms (Wu et al 2010). Our study adds to the previous articles by focusing on the timing of initiation of alcohol use, specifically, early (by age 14) initiation, a strong indicator of future risk (DeWit et al 2000), by considering childhood adversities in the context of multiple and cumulative risks, and by examining the role of gender and sociocultural context in these associations.…”
Section: The Current Studymentioning
confidence: 99%
“…One focused on depressive symptoms (Wu et al 2006) and another on trauma and post-traumatic stress disorder symptoms (Wu et al 2010). Our study adds to the previous articles by focusing on the timing of initiation of alcohol use, specifically, early (by age 14) initiation, a strong indicator of future risk (DeWit et al 2000), by considering childhood adversities in the context of multiple and cumulative risks, and by examining the role of gender and sociocultural context in these associations.…”
Section: The Current Studymentioning
confidence: 99%
“…------IJADR 1(1) ------80 & Randall, 2003;Morris, Stewart, & Ham, 2005;Schneier et al, 2010;Zimmermann et al, 2003), posttraumatic stress disorder or symptoms (Blume, Resor, Villanueva, & Braddy, 2009;Jacobson et al, 2008;McDevitt-Murphy et al, 2010), physical pain (Lawton & Simpson, 2009;Moos, Brennan, Schutte, & Moos, 2010;Riley & King, 2009), cumulative experience with stressful life events (Aseltine & Gore, 2000;Dawson, Grant, & Ruan, 2005;Lloyd & Turner, 2008), after-effects of military combat (Jacobsen et al, 2008;Šakušić et al, 2009;Wilk et al, 2010), after-effects of disasters and terrorism (Boscarino, Adams, & Galea, 2006;Grieger, Fullerton, Ursano, & Reeves, 2003;Hasin, Keyes, Hatzenbuehler, Aharonovich, & Alderson, 2007), after-effects of childhood trauma (Sarin & NolenHoeksema, 2010;Wilsnack, Wilsnack, Kristjanson, Vogeltanz-Holm, & Harris, 2004;Wu et al, 2010), after-effects of assault and criminal victimization (Kaysen et al, 2007;Ullman, Filipas, Townsend, & Starzynski, 2005;Vaughn et al, 2010) and chronic negative emotions arising for other reasons (Costanzo et al, 2007;Dorfman, Trokel, Lincoln, & Mehta, 2010;Witkiewitz & Villarroel, 2009). Links between chronic stress and chronic drinking patterns are found more consistently than links between acute but time-limited stress and immediate drinking responses (Armeli, Todd, & Mohr, 2005;Helzer, Badger, Searles, Rose, & Mongeon, 2006;Skaff, Finney, & Moos, 1999; but see also …”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…The diagnosis of PTSD involves experiencing symptoms in three areas in response to a traumatic event: 1) intrusive thoughts that involve a re-experiencing of the trauma, 2) persistent avoidance of trauma-related stimuli or emotional numbing, and 3) persistent symptoms of increased physiological arousal (American Psychiatric Association 2000). Previous researchers have established associations between childhood maltreatment history and PTSD/PTSS in adolescence (e.g., Kingston and Raghavan 2009) and between PTSD/PTSS and substance use (e.g., Lubman et al 2007), with prospective investigations postulating that PTSD/PTSS in most cases precedes substance use (Wu et al 2010). Lipschitz et al (2003) found that within a sample of inner-city adolescents, PTSS predicted substance use, with PTSS being identified as preceding substance use.…”
mentioning
confidence: 99%